Anatomia da raiz de oito espécies de macrófitas aquáticas emergentes da planície alagável do alto rio Paraná. - Marques, Ângela Maria Marques Sanches (2008)
The floodplain of the high Paraná river is characterized by the existence of several aquatic and transitional habitats among the aquatic and terrestrial environment, influencing in the presence and distribution of the aquatic macrophyte. With the objective of comparing the anatomy of the roots of eight species of emerging aquatic macrophyte, sampling were accomplished in different places and prepared permanent slides for analysis and capture of images. The species possess epidermis uniseriate of narrow and long cells, cortex composed by exodermis uniseriate or biseriate, with or without thickening, aerenchyma with great gaps, endodermis uniseriate, with or without thickening, continuous pericycle or interrupted and central cylinder with variable number of xylem poles.